2017
DOI: 10.1021/acsphotonics.7b01018
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Light Absorption with Various Nanostructure Geometries in Vertically Aligned Si Nanowire Arrays

Abstract: Exploring the interactions between light and nanostructures contributes greatly to understanding and engineering nanoscale optical phenomena related to device performance. However, this often involves a compromise between uniformity and scalability. Given that optical properties, and especially light absorption, are governed by the geometries of nanostructures, this study investigated the correlation between light absorption and vertically aligned silicon nanowire (v-SiNW) arrays synthesized using KrF stepper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Ultraviolet-visible (UV-Vis) relative differential reflectance spectra analysis in SI Appendix, Fig. S20 shows that GaN NWs enhance the sunlight absorption of the n + -p silicon junction in a wide wavelength range, due to the light trapping effect (57). In addition, as shown in the energy diagram in SI Appendix, Fig.…”
Section: Synthesis and Characterization Of The Binary Cufe Electrocatmentioning
confidence: 96%
“…Ultraviolet-visible (UV-Vis) relative differential reflectance spectra analysis in SI Appendix, Fig. S20 shows that GaN NWs enhance the sunlight absorption of the n + -p silicon junction in a wide wavelength range, due to the light trapping effect (57). In addition, as shown in the energy diagram in SI Appendix, Fig.…”
Section: Synthesis and Characterization Of The Binary Cufe Electrocatmentioning
confidence: 96%
“…To understand this difference, we studied the morphology of the etched structures. Even minor changes in morphology are known to significantly affect the optical absorption of NWs. Thus, we performed SEM on NWs after forcing In 2 O 3 /SiNWs to lay horizontally on the substrate for a thorough inspection of morphology. Detailed SEM images of such In 2 O 3 -coated SiNWs are provided in the Supporting Information Figure S9.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, the evaluation of light absorption of single micro/nanowires relies either on indirect measurement or theoretical models, which can only provide qualitative values 28 35 . Experimental methods for probing light absorption such as monitoring the photocurrent generated within single wire devices are time-consuming and require complicated microelectrodes fabrication process 36 41 . In addition, we have shown that the real nanowire absorption deviates significantly from the theoretical prediction calling for caution in using these equations or simulation results.…”
Section: Resultsmentioning
confidence: 99%